Strategi Meningkatkan Budaya Literasi Dalam Pengembangan Perpustakaan Sekolah Di SMK Negeri 2 Samarinda - Dwisari Harumningtyas (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2022)
literacy culture in schools is an important thing to develop, especially with regard to reading and writing activities. Through reading students can think critically and obtain a lot of information from various countries. The existence of a school library is very important to support literacy activities and the teaching and learning process carried out by teachers and students. The school library contains textbooks or reading materials and the work of school members, both teachers and students, which are arranged in such a way, administered and organized in a certain way to provide convenience for users as information material. In carrying out library development at SMK Negeri 2 Samarinda, it experienced several obstacles, including (1) the low competence of human resources for library management, (2) limited school budgets for developing school libraries, and (3) limited supporting facilities and infrastructure. There are also ways to overcome these obstacles, namely (1) involving the head of the library in education and training, (2) conducting working visits to school libraries and regional libraries, (3) submitting a proposal to add library collections to the company, and (4) inventorying library needs which are then submitted in the 2023 school budget. For the development of the library at SMK Negeri 2 Samarinda, in addition to adding library collections and information technology-based equipment, the library was further developed into a modern library. A modern library is a library that has been computerized for all processing, service and dissemination of information on its library materials.